The green bicycle - Al-Mansour, Haifaa 1974- (Listening Library/Penguin Random House Audio, 2015)
Spunky eleven-year-old Wadjda lives in Riyadh, Saudi Arabia with her parents. She desperately wants a bicycle so that she can race her friend Abdullah, even though it is considered improper for girls to ride bikes. Wadjda earns money for her dream bike by selling homemade bracelets and mixtapes of banned music to her classmates. But after she's caught, she's forced to turn over a new leaf (sort of), or risk expulsion from school. Still, Wadjda keeps scheming, and with the bicycle so closely in her sights, she will stop at nothing to get what she wants
Compact discs. - "Based on the award-winning film Wadjda"--Container
Keywords: Girls / Saudi Arabia / Social conditions / Juvenile fiction; Bicycles / Saudi Arabia / Juvenile fiction; Mothers and daughters / Saudi Arabia / Juvenile fiction; Contests / Saudi Arabia / Juvenile fiction; Bicycle racing / Saudi Arabia / Riyadh / Juvenile fiction; Girls / Conduct of life / Juvenile fiction; Parents / Juvenile fiction; Girls / Conduct of life / Fiction; Parents / Fiction; Bicycle racing / Saudi Arabia / Riyadh / Fiction; Bicycle racing; Bicycles; Contests; Girls / Conduct of life; Girls / Social conditions; Mothers and daughters; Parents; Fahrrad; Wunsch; Soziale Probleme; Junge; Freundschaft; Mädchen; Saudi Arabia / Juvenile fiction; Saudi Arabia; Saudi Arabia / Riyadh; Riad; Hörbuch; CD